2019
DOI: 10.1038/s41598-019-39828-5
|View full text |Cite
|
Sign up to set email alerts
|

Cross-disease analysis of Alzheimer’s disease and type-2 Diabetes highlights the role of autophagy in the pathophysiology of two highly comorbid diseases

Abstract: Evidence is accumulating that the main chronic diseases of aging Alzheimer’s disease (AD) and type-2 diabetes mellitus (T2DM) share common pathophysiological mechanisms. This study aimed at applying systems biology approaches to increase the knowledge of the shared molecular pathways underpinnings of AD and T2DM. We analysed transcriptomic data of post-mortem AD and T2DM human brains to obtain disease signatures of AD and T2DM and combined them with protein-protein interaction information to construct two dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 80 publications
1
42
0
Order By: Relevance
“…A recent study analyzed transcriptomics data of post-mortem brains of Alzheimer's and type 2 diabetes patients. Data analysis indicated a principal role for autophagy dysfunction in both diseases (Caberlotto et al, 2019). The role of autophagy-related genes was confirmed using an Alzheimer mouse model.…”
Section: Alzheimer's Diseasementioning
confidence: 78%
“…A recent study analyzed transcriptomics data of post-mortem brains of Alzheimer's and type 2 diabetes patients. Data analysis indicated a principal role for autophagy dysfunction in both diseases (Caberlotto et al, 2019). The role of autophagy-related genes was confirmed using an Alzheimer mouse model.…”
Section: Alzheimer's Diseasementioning
confidence: 78%
“…Moreover, in an insulin‐deficient mice model, phosphorylation of GSK‐3α and GSK‐3β levels showed a significant fall in 9 weeks old diabetic brain (Jolivalt et al, ). Other than the insulin signaling pathway, there is a recent report which shows deregulation of autophagy and its related genes to be involved in the pathophysiology of two diseases (Caberlotto et al, ).…”
Section: Possible Mechanism Underlying the Connectionmentioning
confidence: 99%
“…Alzheimer's disease (AD) is a progressive neurodegenerative disease clinically characterized by cognitive, functional, and behavioral alterations. It is also characterized by histopathological, molecular, and biochemical abnormalities such as cell loss, intracellular accumulation of neurofibrillary tangles, dystrophic neurites, amyloid-β deposits, deranged energy metabolism, mitochondrial dysfunction, chronic oxidative stress, and DNA damage [1]. Of these pathologic changes, intracellular accumulation of neurofibrillary tangles is both spatially and temporally closely associated with neuronal degeneration and cognitive symptoms [2].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin is found to inhibit amyloid-β generation and to prevent hyperphosphorylation of tau protein (the main pathologic hallmark of AD) [16,17]. In contrast, insulin resistance and insulin deficiency are associated with the increased extracellular amyloid-β accumulation and intracellular hyperphosphorylated tau [1,[18][19][20]. Postmortem studies showed decreased synaptic plasticity in T2DM patients [21], and other studies showed insulin administration to improve synaptic formation [22,23] and cognitive performance [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation